Meningkatkan Minat Belajar Siswa dengan Menggunakan Media Bergambar dan Power Point Pada Mata Pelajaran Fiqih - Selamat Pohan; Mavianti Mavianti; Hasrian Rudi Setiawan; Abdul Halim Marpaung (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
The development of the times that cannot be separated from technology certainly demands the human ability to master the technology. The world of education is also not spared from these technological developments. In this case, of course, the teacher must also be qualified in mastering technology in order to be able to present interesting learning materials for students. However, problems also began to emerge, especially in children's interest in learning, which seemed stagnant. This is caused by several factors such as monotonous learning carried out by teachers who are not at peace with technological developments. This study aims to increase children's interest in learning by using pictorial media and power point. The research method used is quantitative research with purposive sampling technique. The results of the study are: children are interested in learning after using pictorial media on subjects at Madinatussalam School are very interested based on the results of the study, it can be proven by an average value of 28,85. with the number of respondents as many as 20 children. Based on the findings of the test data that has been carried out, it can be concluded that Ha (alternative hypothesis) is accepted, that is, there are differences in children's learning interest for those who use illustrated learning media than those who use power point media in learning.